Effect of Feeding Moringa oleifera Meal on Growth Performance of Growing Surti Kids under Intensive System of Management - Pandey, Anushri; Modi, Rakesh J.; Lunagariya, Pravin M.; Islam, Manzarul (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A 14 weeks study was carried out on eighteen Surti kids of 6-8 months of age. The kids were randomly divided into three treatment groups, with six in each group based on the same age and uniform conformation to evaluate the effect of Moringa oleifera meal (MOM) on growth performance. After 15 days of the adaptation period, kids were offered total mixed ration (TMR) by replacing commercial concentrate with MOM at 0, 25, and 50 % inclusion rates by maintaining a constant protein level in all the dietary rations. The results showed that kids fed on three different inclusion rates of M. oleifera meal in concentrate did not reveal significant differences in their overall body weight, total body weight gain, and biometry (body length and heart girth), except height at wither, which was significantly (p <0.05) higher at 50 % of inclusion rate as compared to 25 % of inclusion rate. The average daily body weight gain was significantly (p <0.05) higher at 25 % MOM inclusion. It was concluded that feeding MOM by replacing commercial concentrate mixture does not impair overall body weight and biometry and improves the average daily body weight gain of Surti kids. The best result on growth performance was shown by the goats fed on 25 % MOM.